Optimizing SiDesa and Making Ant Sugar as a Functional Food Product with High Economic Value - Umar, Fitriani; Amanda, Riska; Rahmat, Muh. Ibnu Alfarizi; Faizah, Nur; Heriani, Heriani; Jagad, Sapu; Suwardi, Suwardi; Samsuriadi, Samsuriadi (Sarana Ilmu Indonesia (salnesia), 2025)
Abstract The Village Information System (SiDesa) was developed to facilitate data management, administrative services, and communication between the village government and the community. In addition, it served as a platform to promote local potential in the village area. The purpose of this community service activity was to optimize the use of SiDesa and enhance local potential through the socialization of palm sugar granule (ant sugar) production as a functional food. This activity was part of a thematic KKN (student community service) program conducted by students of Universitas Muhammadiyah Parepare, located in Benteng Paremba Village, Lembang District, Pinrang Regency. The implementation of the program included population data collection and content entry into the SiDesa website. Local potential development was carried out by socializing the process of converting brown sugar into ant sugar, a functional food product with high economic value. The activity involved training local residents on how to produce ant sugar. The production process began by grinding the brown sugar, cooking it over medium heat until it melted, then turning off the stove while stirring the mixture until it solidified and dried, after which it was filtered and packaged. As a result of this program, the use of SiDesa was expected to become more optimal in providing complete village profile information, facilitating administrative procedures for residents, and serving as a promotional tool for local potential and tourism in Benteng Paremba Village.